Aspirin administration by emergency medical dispatchers using a protocol-driven aspirin diagnostic and instruction tool. Issue 7 (25th July 2012) - Barron, Tracey; Clawson, Jeff; Scott, Greg; Patterson, Brett; Shiner, Ronald; Robinson, Donald; Wrigley, Fenella; Gummett, James; Olola, Christopher H O
Abstract : Background: The American College of Cardiology and the American Heart Association recommend early aspirin administration to patients with symptoms of acute coronary syndrome (ACS)/acute myocardial infarction (AMI). The primary objective of this study was to determine if Emergency Medical Dispatchers (EMD) can provide chest pain/heart attack patients with standardised instructions effectively, using an aspirin diagnostic and instruction tool (ADxT) within the Medical Priority Dispatch System (MPDS) before arrival of an emergency response crew. Methods: This retrospective study involved three dispatch centres in the UK and USA. We analysed 6 months of data involving chest pain/heart attack symptoms taken using the MPDS chest pain and heart problems/automated internal cardiac defibrillator protocols. Results: The EMDs successfully completed the ADxT on 69.8% of the 44 141 cases analysed. The patient's mean age was higher when the ADxT was completed, than when it was not (mean±SD: 53.9±19.9 and 49.9±20.2; p<0.001, respectively). The ADxT completion rate was higher for second-party than first-party calls (70.3% and 69.0%; p=0.024, respectively). A higher percentage of male than female patients took aspirin (91.3% and 88.9%; p=0.001, respectively). Patients who took aspirin were significantly younger than those who did not (mean±SD: 61.8±17.5 and 64.7±17.9, respectively). Unavailability of aspirin was the major reason (44.4%) why eligible patients did not take aspirin when advised. Conclusions: EMDs, using a standardised protocol, can enable early aspirin therapy to treat potential ACS/AMI prior to responders' arrival. Further research is required to assess reasons for not using the protocol, and the significance of the various associations discovered.